Mapping the NFYA 3′UTR landscape identifies alternative polyadenylation as a targetable vulnerability in prostate cancer - Giulia Pagani; Chiara Casirati; Cecilia Pandini; Stefania Fornezza; Chiara Priami; Giulia Fois; Sara Bisi; Aleksei Mironov; Roberta Cacioppo; Nicola Manfrini; Mihaela Zavolan; Francesco Nicassio; et al. (Journal of Experimental & Clinical Cancer Research, 2026)
Abstract Background Alternative polyadenylation (APA) is increasingly recognized as a pervasive oncogenic mechanism that reshapes post-transcriptional gene regulation and promotes tumor aggressiveness. Whether APA contributes to the dysregulation of NFYA —encoding the regulatory subunit of the oncogenic transcription factor NF-Y—in prostate cancer (PCa) remains largely uncharacterized. Methods We interrogated bulk, single cell and 3’-end RNA-sequencing data from PCa cell lines and patient samples to re-annotate and quantify the usage of NFYA 3′UTRs. The functional consequences of APA were assessed using reporter assays. NFYA APA was experimentally reprogrammed using CRISPR/Cas9-mediated deletion and antisense oligonucleotide (ASO)-based masking of polyadenylation signals, followed by in vitro and in vivo phenotypic analyses. Results Four functional NFYA 3′UTR isoforms were identified, with one predominantly used across cell lines and tissues. PCa displayed pervasive NFYA 3′UTR shortening, which correlated with tumor grade and metastatic disease, increased NF-YA protein abundance, and enhanced proliferation. 3′UTR lengthening was instead observed upon induction of cellular quiescence or after Enzalutamide treatment. Mechanistically, 3′UTR lengthening reduced NF-YA protein expression through decreased mRNA stability, impaired translation, and enhanced nuclear retention, rather than increased miRNA-mediated repression. Enforced NFYA 3′UTR lengthening in PCa cells via CRISPR/Cas9 or ASOs diminished NF-YA protein levels and suppressed aggressive tumor traits both in vitro and in vivo. Conclusions These findings establish NFYA APA as a critical determinant of NF-YA oncogenic output and downstream tumor-promoting programs, and as a previously unrecognized driver of PCa progression. Importantly, they provide proof-of-concept for gene-specific, APA-directed therapeutic strategies. ASO-mediated modulation of polyadenylation indeed emerges as a clinically translatable approach to fine-tune oncogene expression, thus opening new avenues for RNA-based precision interventions in aggressive PCa.